Dosing patterns and dose effects of sacubitril/valsartan: A claims-based retrospective cohort study. - Jillian M Rung; Tyson S Barrett; Keith LeJeune; Shannon B Richards; Amresh Raina; Lawrence Sinoway (PLoS ONE)
Purpose The goals of this retrospective cohort analysis were to determine real-world dose and titration patterns of sacubitril/valsartan (SAC/VAL), a heart failure medication, and examine whether dose patterns are associated with healthcare utilization and costs. Methods Adult health plan members (18-100 years old) who initiated SAC/VAL between 2020 and 2022 and had continuous enrollment 6 months prior to, and at least 3 months following SAC/VAL initiation were identified. Members also had to have 3 months of SAC/VAL fills with good adherence (N =  2,977). Claims data were used to characterize dosage patterns and compare total costs of care, as well as all-cause and heart failure- hospital admissions across those with different terminal SAC/VAL doses. Results Most members initiated SAC/VAL at the lowest dose (76%, n =  2,267), of whom few titrated upward by their final fill (31%, n =  703). Overall, only 19% (n =  563) were at target by their final fill. Those ending on higher doses experienced significantly fewer all-cause admissions (incidence rate ratios of 1.52 [SE = .16] to 2.66 [SE = .37]; ps < .001) and incurred significantly lower total costs of care while on SAC/VAL (cost ratios of 1.21 [SE = .06] to 1.48 [SE = .09]; ps < .001). Conclusion Most individuals initiate and remain on the lowest SAC/VAL dose despite guidelines to titrate upward. SAC/VAL dosage is significantly associated with outcomes, with higher doses associated with more clinical and cost benefits. Research is needed to identify barriers to dose titration and to develop interventions for maximal patient benefit.